Faktor-faktor yang mempengaruhi kebijakan hutang perusahaan non keuangan publik - SORAYA SORAYA; MEIRYANANDA PERMANASARI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to get an empirical evidence about influence of non-debt tax shield, tangibility, profitability, growth, size, manajerial ownership, institutional ownership, dividend policy, business risk, and investment opportunity set on debt policy. The population of this research are allnon financial companies listed in Indonesia Stock Exchange (IDX) from the period of 2010 to 2013. Sample selection procedure carried out by implementing purposive sampling method with total sample 33 non financial companies. Data are analyzed using multiple regression analysis. The result indicates that non-debt tax shield, tangibility, profitability, growth, size, institutional ownership, and dividend policy have influence toward debt policy. Other independent variables such as manajerial ownership, business risk, and investment opportunity set do not have influence toward debt policy.